A review analysis of corrosion rate on stainless steel pipe in sea water media - Alfattah, Muhammad; Arwati, I Gusti Ayu; Majlan, Edy Herianto (SINERGI, 2024)
Regarding providing energy, few sectors are as massive as the oil and gas business. One of the most crucial parts of oil and gas production is the distribution pipes or pipelines that transport the production fluids, which include oil and gas, from one distribution point to another. The corrosion of A316 material, which can lead to holes or pitting, and the damage it causes in most industrial operations, particularly in the oil and gas industry, has resulted in substantial losses at high prices over an extended period of time. In the study, we will quickly examine what corrosion is, the different kinds of corrosion, inhibitors, and how to assess the corrosion rate of A316 stainless steel in salt water. Analysis of the electrochemical corrosion rate of Inconel 600 nickel alloy and stainless steel 316L subjected to varying amounts of saltwater (freshwater, seawater, mixed water). Because chlorine speeds up corrosion, alloys like Inconel 600 and 316L undergo pitting corrosion. The molybdenum component gives 316 stainless steel its superior corrosion resistance. That's why it works well for gas and oil pipelines that go through saltwater. Nevertheless, materials exposed to maritime environments must have cathodic protection or coating to prolong their life and stop the pipe from continuously corroding.